HOMEOPATHY AND HOMEOPATHIC MEDICINES - Gavrilovic, Ivana; Jelikić-Stankov, Milena (ACADEMIC REVIEW, 2020)
The purpose of this publication is to present homeopathy as a current and recognised method of alternative medicine. The mechanism of action of homeopathic medicines has been described taking into account certain contradictions regarding physical and chemical properties of the compounds and chemicals that are used for their preparation. Special attention has been given to homeopathic remedies described in pharmacopoeias such as German, as well as protocols for using homeopathic remedies based on many years of experience and clinical studies. A few homeopathic remedies of plant origin were listed and their application in treating diseases where the conventional medicine did not yield the expected outcomes. Homeopathic remedies prepared from toxic metals by specific procedures were described, but once prepared, these are used in personalised homeopathic therapy according to the strictly established protocols. Specificity and quality control including the state-of-the-art analytical methods were illustrated by several examples.